Penyelesaian Penjadwalan Flexible Job Shop Problem Menggunakan Real Coded Genetic Algorithm - M Chandra Cahyo Utomo; Wayan Firdaus Mahmudy; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Scheduling is a problem that is quite difficult if it should be prosecuted in quick time and will be more troublesome if the arrangement is scheduled for something uncertain with many options that require a more complicated decision. Jobshop scheduling model is one example of scheduling problems that were encountered in the manufacturing industry. Completion of complex problem and the best solution can only be obtained by trying all possibilities. Genetic algorithm is one of algorithms which can provide complex solutions to problems within acceptable time rationally, so that it can be applied to the Flexible Job Shop problem. Genetic Algorithm is able to take into account by trying to exchange arrangements provided and/or try to replace the array directly (crossover and/or mutation).